1990
DOI: 10.1002/cne.902930404
|View full text |Cite
|
Sign up to set email alerts
|

Connections of the parabrachial nucleus with the nucleus of the solitary tract and the medullary reticular formation in the rat

Abstract: We examined the subnuclear organization of projections to the parabrachial nucleus (PB) from the nucleus of the solitary tract (NTS), area postrema, and medullary reticular formation in the rat by using the anterograde and retrograde transport of wheat germ agglutinin-horseradish peroxidase conjugate and anterograde tracing with Phaseolus vulgaris-leucoagglutinin. Different functional regions of the NTS/area postrema complex and medullary reticular formation were found to innervate largely nonoverlapping zones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
676
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 911 publications
(726 citation statements)
references
References 87 publications
47
676
3
Order By: Relevance
“…The precise role of pontine neurons in respiratory modulation remains unclear since stimulation of different regions of the dorsolateral pons can result in tachypnea, bradypnea, apneusis or apnoea (Chamberlin and Saper, 1994;Fung and St John, 1994;Mutolo et al, 1998). Neurones within the dorsolateral pons have reciprocal connections, some via the ventrolateral pons (Herbert et al, 1990;Song and Poon, 2004), with respiratory neurones within the ventrolateral medulla (Ellenberger and Feldman, 1990;Herbert et al, 1990;Song and Poon, 2004), and some of these neurones project to the nucleus tractus solitarius (Herbert et al, 1990) and phrenic motoneurones (Yokota et al, 2001). Evidence for whether respiratory rhythmic output persists during breath holding is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise role of pontine neurons in respiratory modulation remains unclear since stimulation of different regions of the dorsolateral pons can result in tachypnea, bradypnea, apneusis or apnoea (Chamberlin and Saper, 1994;Fung and St John, 1994;Mutolo et al, 1998). Neurones within the dorsolateral pons have reciprocal connections, some via the ventrolateral pons (Herbert et al, 1990;Song and Poon, 2004), with respiratory neurones within the ventrolateral medulla (Ellenberger and Feldman, 1990;Herbert et al, 1990;Song and Poon, 2004), and some of these neurones project to the nucleus tractus solitarius (Herbert et al, 1990) and phrenic motoneurones (Yokota et al, 2001). Evidence for whether respiratory rhythmic output persists during breath holding is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal fibres transmitting afferent information from the lungs, chest wall and respiratory muscles as a result of lung inflation, project to and terminate onto neurones within the nucleus of the solitary tract (Bianchi et al, 1995), which in turn project to the parabrachial nucleus (Cechetto, 1995;Herbert et al, 1990). Although it is possible that the pontine activity identified in this study reflects sensory feedback from the lungs, we think this is unlikely because the protocol was designed to minimise afferent signalling by performing the breath hold at resting expiratory lung volume (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested later that the major neural target of the AP might be a specific region within the LPb, the external subdivision (van der Kooy and Koda, 1983; Cunningham et aL, 1994). Herbert et al (1990) used an anterogarde tracing technique to examine the subnuclear organization of the AP-Pb projection in the rat. According to their findings, the core of the AP projected to the central, external, and dorsal subdivisions of the LPb.…”
Section: Projections From the Apmentioning
confidence: 99%
“…Based on physiological studies, the AP has generally been recognized to act as a "chemoreceptor trigger zone" for the induction of emesis (Borison et al, 1984;Carpenter, 1989), however, there have been few morphological studies concerning the neuronal mechanisms which underlie the emetic reflex via the AP. Some studies have reported on the nature of the connectivity of the AP, but most have used the rat as their model, which, unlike the suncus, is not prone to vomiting (van der Kooy and Koda, 1983; Shapiro and Miselis, 1985a;Herbert et aL, 1990;Cunningham et aL, 1994). In the ferret, a species with a high incidence of vomiting, Strominger et aL (1994) demonstrated that the AP has reciprocal connections only with the nucleus of the solitary tract (NTS), which is generally accepted as the primary recipient of gustatory, cardiovascular, pulmonary, and gastrointestinal sensory afferents.…”
mentioning
confidence: 99%
“…The medial NTS (mNTS) and the commissural NTS (commNTS) subnuclei project to the forebrain areas involved in the control of hydroelectrolyte balance, such as the paraventricular nucleus and the anteroventral third ventricle region and to hindbrain areas such as the LPBN (14)(15)(16) and receive projections from the AP (17). Besides playing a well-established role in cardiovascular regulation (18)(19)(20), the NTS may also be involved in the control of fluid balance.…”
Section: Introductionmentioning
confidence: 99%